DESARROLLO INTEGRAL SUSTENTABLE DE LOS VALLES ALTOS DEL ESTADO CARABOBO DESDE LA PERSPECTIVA DEL CONSTRUCCIONISMO SOCIAL (Agroindustria, Sociedad y Ambiente, 2021)
To emerging changes in the agricultural sector, it is necessary to implement guidelines that promote productivity in organizations linked to commodity activity in the contributory echoes of sustainable development, promoting an approach of creativity towards new systems of ecological viability, social equity and economic profitability, to expose forms of value added through the identification of synergistic effects of the network of interrelations. The purpose of the study was to formulate strategic guidelines for developing programmes and projects in the context of food security and agricultural development in the Valleys High of Carabobo (municipalities Bejuma, Miranda and Montalbán), based on the diagnosis territorial using Multicriteria evaluation and GIS support of geomatics. A social constructionist approach, research is phenomenological, supported in hermeneutics. Resulted in a set of guidelines for the design of programmes and projects from the specified dimensions (environmental education, training and agrogestion, Agroecology, generating added value and support activities from the institutional framework), as articulators mechanisms for the promotion of the competitiveness of the agricultural sector, with revenues in the organization, training of producers, commodity diversification, local environmental improvements and quality of life. From this perspective, it highlights the importance observed in relation to processes of organization and training in the context of agriculture, fire the participation of actors from the institutional and social representation, to extend the revenues on the status of sectoral competitiveness arising from the implementation of programs associated with the strategic guidelines which are exposed.
Keywords: Social constructionism, agricultural productivity, Carabobo's High Valleys.